CAN NUTRITIONAL INTERVENTIONS CURB OBESITY? A STUDY AGAINST STANDARD CARE AND NO TREATMENT (Journal of Medical & Health Sciences Review, 2025)
Obesity is an epidemic health issue in the world with serious medical, social and economic implications. Although the problem is well known to be associated with risks, classical clinical practice that in most cases merely provides patients with a few dieting tips has not been particularly successful. The present paper examines the topic of the study of whether structured nutritional interventions provide better results in the reduction of obesity than standard care and no intervention. To compare the nutritional interventions to control body weight and enhance the metabolic outcomes, compared to usual medical care and passive or no-treatment situations, a narrative-compared synthesis of 33 peer-reviewed articles was made (randomized controlled trials, cohort analysis, and systematic reviews). The study was categorized into three namely, nutritional interventions, standard care and no treatment. The most important outcome measures were weight loss, the change in BMI, HbA1c, blood pressure, adherence to diets, and effectiveness across the demographic groups. The average weight loss and reduction of BMI was 4 to 10 kg and 1.5 to 3.5 units in participants using intervention arms. Also, metabolic indicators, including HbA1c and blood pressure, were recorded to be improved more sharply. Behavioral support and mobile health-based interventions had the greatest adherence rates. Conversely, there were modest effects which were derived due to standard care and no-treatment groups usually gained weight or even their metabolic conditions worsened They need to be integrated in the public health systems and clinical practice with a focus on scalable and sustainable augmented weight management and metabolic health. Future studies on the subject matter should be based on the long-term adherence, equity-based approaches, and digital delivery models.